2013
DOI: 10.1007/s10853-013-7444-0
|View full text |Cite
|
Sign up to set email alerts
|

Effect of porosity on the crack pattern and residual strength of ceramics after quenching

Abstract: The effect of porosity on the crack characteristics of ceramics after water-quenching is studied by measuring the cracks in ceramic sheets. The result reveals that the pore volume fraction has a slight effect on the enhancement of thermal shock resistance of ceramics when the porosity ranges from 0 to 20 %, because the length and density of the long crack in porous alumina are always slightly less than that in dense alumina. This result is in agreement with the prediction based on the minimum potential energy … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Inspired by Bahr's research works, in the last decade, many researchers studied crack patterns after thermal shocks, in order to reveal mechanisms between residual strength and crack characteristics . For thin ceramic specimens, Shao conducted thermal shock testing in the temperature range higher than the critical thermal shock temperature difference (Δ T c ) and showed that the depth of long crack was gradually increased in regime III, which supported the standpoint of Davidge and Bahr, although Hasselman had opposite results.…”
Section: Introductionmentioning
confidence: 86%
“…Inspired by Bahr's research works, in the last decade, many researchers studied crack patterns after thermal shocks, in order to reveal mechanisms between residual strength and crack characteristics . For thin ceramic specimens, Shao conducted thermal shock testing in the temperature range higher than the critical thermal shock temperature difference (Δ T c ) and showed that the depth of long crack was gradually increased in regime III, which supported the standpoint of Davidge and Bahr, although Hasselman had opposite results.…”
Section: Introductionmentioning
confidence: 86%
“…However, the pore volume fraction has a slight effect on the enhancement of thermal shock resistance, especially when the porosity of ceramic composite is <10%. 26 Secondly, the changing trends of mechanical properties also have an efficient influence on the thermal shock resistance. In theory, models of thermal shock behavior usually fall into two categories: one is thermal stress fracture resistance parameter, R, and the other one is the thermal stress damage resistance parameter, R IV .…”
Section: Resultsmentioning
confidence: 99%
“…It is attributed that the cracks must spread out around pores and do not simply cut through them when some pores exist in the composite, the crack propagation requires more fracture energy due to stress field relaxation and crack‐tip deflection. However, the pore volume fraction has a slight effect on the enhancement of thermal shock resistance, especially when the porosity of ceramic composite is <10% …”
Section: Thermal Shock Parameters Of Bn‐zro2‐sic Composites With Diffmentioning
confidence: 99%
“…Note that fracture toughness was not measured for specimens PM-HP-673 (P = 0.30) or PM-HP-673-Ag (P = 0.27) since these specimens were too fragile to be polished. In the literature, it has been noted that K C can increase, decrease, or remain unchanged with increasing P [59,68].…”
Section: Hardness and Fracture Toughness As Function Of Porositymentioning
confidence: 99%